Computational fluid dynamic modelling of an electric furnace used in the smelting of PGM containing concentrates - Bezuidenhout, J.; Eksteen, Jacques; Bradshaw, S. (Elsevier, 2009)
A complete three-dimensional computational fluid dynamic model has been developed to investigate the internal dynamics of a circular, three-phase electrical furnace as used for the smelting of Platinum Group Metal (PGM) concentrates. The model included multi-phase interactions between multiple fluid layers and CO-gas bubble release from the immersed electrode surface while three-phase AC electrical current was simulated at the electrodes. The model further accounts for the heat associated with the melting of concentrate which was thermodynamically calculated and incorporated by assuming zones of varying smelting intensity within the concentrate layer. The relationship between electrode immersion depths, at 15%, 35% and 55% in the slag, and the current distribution and slag electrical resistivity has been quantified while the temperature and velocity fields were obtained for 35% electrode immersion model, a typical operation case. The slag was identified as being at a fairly uniform temperature due to the mixing induced by natural buoyancy and the CO-bubble-momentum with the highest flow noted between and directly around the electrodes. The matte showed a stratified temperature distribution with little flow activity. The model results were found to correlate well with previously published studies and actual operating parameters. © 2009 Elsevier Ltd. All rights reserved.